Pengaruh Kepemimpinan dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Sawahlunto - Rio Nardo; Adella Haryani (Fakultas Sastra Universitas Ekasakti, 2021)
Human resources is the main focus of all organization in order to reach the goals. For Human resources is the major factor as the success of bussiness is depended on it, so that, the Job Satisfaction of human resources or the employee had to have more concern by organization. This study aims to determine how much influence the Leadership and Physical Work Environment on Job Satisfaction in the BKPSDM Sawahlunto City. The population amounted to 41 employees. Sampling is saturated sample by making the entire population being sampled. Data retrieval in the form of questionnaire. Using Multiple Regression Analysis. Th result of this study are leadership has positive and significant impact on the job satisfaction and Physical Work Environment has positive and significant impact on the job satisfaction.